Effects of attachments on aerodynamic characteristics and vortex-induced vibration of twin-box girder. (February 2018) - Laima, Shujin; Li, Hui; Chen, Wenli; Ou, Jinping
Abstract: An experimental investigation was carried out on the effects of attachments on the aerodynamic characteristics and vortex-induced vibration (VIV) of a twin-box girder. In the study, the flow pattern, pressure distribution, vortex shedding frequency, and VIV of five models, namely Model A (twin-box girder without attachments), Model B (twin-box girder with handrails and crash barriers), Model C (twin-box girder with handrails, crash barriers, and wind barriers), Model D (twin-box girder with maintenance rails), and Model E (twin-box girder with full ancillaries), are compared with a bare deck in detail. The results demonstrate that, owing to the large leading flow separation induced by the attachments, the flow characteristics and VIVs of the twin-box girder with attachments differ considerably from the bare twin-box girder. Because of the large porous ratio, the handrails and crash barriers exert relatively weak influences on the surface pressure distribution. However, the leading wind barrier and maintenance rail generate large flow separation at the leading edges, resulting in larger pressure fluctuations, a wider wake, and larger scale vortex with lower shedding frequency than that of the bare deck. Furthermore, owing to the large leading flow separation, the vertical VIV induced by the motion-induced vortex in the gap is suppressed. However, a torsional VIV is generated by the large-scale alternately shedding vortex in the wake of the downstream box girder.